Supply Chain Analysis Of Gandus Modern Beef Ruminant Ash Products Throught Modern Market In Palembang City - Santika, Dewi; Junaidi, Yulian (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2023)
The objectives of this study are (1) Analyzing product flows, financial flows and information flows in the beef supply chain at the modern market in Palembang City. (2) Analyzing efficiency in the beef supply chain at the modern market in Palembang City. This research was conducted in the modern market in Palembang City. Data collection was carried out in January 2023. The method used is the survey method, which collects information from a sample by asking through a questionnaire or other aids that contain questions related to research. The sampling method used in this study is the purposive sample and accidental sample methods. The data collected in this study are primary data and secondary data. The supply chain for beef in the modern market has one supply chain, namely the flow of products from wholesalers – exchange traders – consumers. For financial flows starting from consumers - exchange traders - wholesalers - RPH. While the flow of information is information related to suppliers, beef purchasing locations, beef quality, beef supply quantities and market prices. The marketing efficiency value of beef from the Gandus Modern Ruminant RPH product is 0.031%, which means it is less than 50%, so it can be said to be efficient.